Integrated DEMNas and Morphogenetic Analysis of Geomorphological Diversity in Salopa, Tasikmalaya, West Java - Ramadan, Ikdan Rifki Muhamad; Rochmana, Yogie Zulkurnia (Universitas Negeri Gorontalo, 2025)
This study presents an integrated geomorphological analysis of the Salopa area in Tasikmalaya Regency, West Java, combining field observations with advanced DEMNas (National Digital Elevation Model). The Salopa area has varied morphology with interesting relief. The diverse morphological features in the Salopa region are evidence of geological processes that have occurred. The focus of this research is to analyze and observe the geomorphology in the study area, aiming to identify the characteristics of the landscape and classify them. This study pioneers the combined use of DEMNas and morphogenetic analysis in Salopa, revealing seven landform units and their tectonic-fluvial interactions. Findings provide a baseline for landslide hazard mapping and sustainable land-use planning in West Java. The research methods used include field observation and systematic analytical approach in terms of morphometry, morphography, and morphogenetics, as well as analysis of the National Digital Elevation Model (DEMNas). Denudational High Hills (15%), Denudational Hills (60%), Structural Hills, Alluvial Plains (6%), Floodplains (10%), Denuded Karst Hills (25%), and Irregular Meander Channels (10%). These units reflect the interplay of tectonic activity, lithological variation, and fluvial processes. The study highlights the dominance of denudational processes, evidenced by landslides and dendritic river patterns, and contrasts the Salopa basin’s geomorphology with adjacent regions like Cibalong.